Literasi Bisnis, Stabilitas Operasional, dan Pemanfaatan Digital Bisnis sebagai Prediktor Efisiensi Ekonomi Komunitas Lokal - Melvin Rahma Sayuga Subroto; Andreas Mahendro Kuncoro; Gigih Aulia Hilmiawan; Anik Puji Handayani (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to analyze the influence of business literacy, operational stability, and digital utilization on the economic efficiency of local communities. The study fills a research gap by simultaneously examining these three predictors within the context of local MSMEs in the Special Region of Yogyakarta (DIY), an area that has received limited attention in prior literature. This research also contributes methodologically through the application of Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze the relationships between variables. Data were collected through a survey of 125 business actors in local communities. The results show that business literacy significantly influences digital utilization (t = 2.539) and operational stability (t = 2.261). Furthermore, digital utilization (t = 6.391) and operational stability (t = 5.094) significantly affect the economic efficiency of local communities. These findings highlight the importance of enhancing business literacy and adopting digital technologies to improve grassroots economic efficiency. In addition to theoretically confirming previous findings, this study also provides new insights into the interrelation of key supporting factors of economic efficiency. The research enriches the literature on community-based MSME development and serves as a reference for more targeted and context-specific small business empowerment policies. The study is limited in geographical scope and sample size, offering opportunities for broader future research.